SISTEM INFORMASI DATA INVENTORI DAN PENJUALAN PADA BENGKEL JAYA ABADI MOTOR NGUTER - Fajar Putra, Yanuar Nur; Anwariningsih, Sri Huning; Retnoningsih, Dwi (2086-4221, 2013)
Inventory data information and selling system is a system that provides the information services includes goods inventory, selling and purchasing transactions. The axistence of information system is important, in this  point, Inventory data information and selling system in Jaya Abadi Motor of Nguter Repair Shop addressed as resarch location, beause system used here still simple and manually, where all the activities of incomin and outcoming goods administering are only recorded in ordinary books. This system had some impacts on time expanded used in data processing, searching, and daily goods selling. Another problem has been raised as mistaken on recording, and this not easy to make investigation to the lost and broken  goods. The aims of this research is to make easier in minimizing good’s also data goods reporting, increasing inventory monitoring therefore, data processing and goods inventory would be controlled better.  Research method used in this study is observation, interview, and literature. Information system used here is Windows 7  operating system, and uses Visual Basic. Net 2005, also Microsoft SQL Server 2005 Software. Research results from this study are an information system of data inventory and selling called: Inventory data information and selling system in Jaya Abadi Motor Repair Shop of Nguter, has made to provide the goods inventory monitoring in Jaya Abadi Motor Repair Shop of Nguter.